Abusive Head Trauma Module in the Child Abuse Pediatrics Curriculum for Physicians (CAP-CuP): Rehma's Story - Katie L. Johnson; Caitlin E. Crumm; Emily C. B. Brown (MedEdPORTAL, 2025)
Introduction Abusive head trauma (AHT) is the leading cause of death from head injuries in children under 2 years and a critically undertaught topic in medical education. Methods We created an interactive module on AHT for medical students, residents, and physicians who treat children. We evaluated the module in three formats: individual, self-paced completion by a multidisciplinary (primarily physician) audience; presentation to a small multidisciplinary (primarily physician) audience at a Child and Adolescent Neurology (CAN) educational conference; and presentation to a large group of first-year medical students as part of a neuropsychology and development course. All versions took 45 minutes. A five-question pre- and postmodule assessment was completed to measure participants’ confidence levels and knowledge pertaining to AHT. Results Twenty-four individual, self-paced participants, 10 CAN educational conference attendees, and 62 medical students participated in the AHT module. Among the largest group (medical students), the median confidence level pertaining to AHT demonstrated a modest increase from 3 (interquartile range [IQR]: 2.00–5.00) to 6 (IQR: 6.00–7.75) on a 10-point Likert-type scale. The proportion of medical students answering knowledge questions correctly increased for every question: 27% to 84%, 50% to 90%, 2% to 90%, and 79% to 96%. Among the audiences composed of primarily physicians (i.e., the CAN conference and individual participants), baseline knowledge and confidence scores tended to be higher than the medical students and exhibited increases for every metric. Discussion This interactive module about AHT was associated with increased confidence and knowledge for a variety of medical audiences and delivery formats.